Analysis Of Home Ownership Credit (KPR) Financing Flpp Prosperity For Customers Low Income (Case Study of Bank BJB Medan Branch Office) - Ishaq, Muhammad Maulana; Widodo, Slamet (Sinergi International Journal of Economics, 2024)
This research aims to evaluate the effectiveness of Sejahtera Home Ownership Credit (KPR) financing through the Housing Financing Liquidity Facility (FLPP) scheme implemented by Bank BJB for Low Income Communities (MBR). The research method used is descriptive qualitative with data collection through in-depth interviews, observation and documentation analysis. The research results show that the FLPP Prosperous KPR program run by Bank BJB has a high level of effectiveness in helping MBR have livable houses. This effectiveness is supported by several factors, including easy access to financing with low interest rates and flexible terms, significant government subsidy support, increasing the welfare of MBR through home ownership, Bank BJB's active role in socialization and education, high levels of realization and customer satisfaction. , as well as good collaboration with developers. With this achievement, the FLPP Prosperous KPR program is proven to be able to provide more affordable financing solutions and contribute to improving the quality of life for MBR. It is hoped that the results of this research can become a reference for developing more inclusive and sustainable banking policies.